The morally disruptive future of reprogenetic enhancement technologies. Issue 5 (May 2023) - Rueda, Jon; Pugh, Jonathan; Savulescu, Julian
Abstract: Emerging reprogenetic technologies may enable the enhancement of our offspring's genes. Beyond raising ethical questions, these biotechnologies may change some aspects of future morality. In the reproductive field, biotechnological innovations may transform moral views about reproductive choices regarding what we consider to be just or even of equal standing.